Analisis Literatur Pengaruh Suku Bunga dan Nilai Tukar terhadap Pergerakan IHSG di Indonesia - Viona Retha Yurianti; Choirul Hamidah (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
The Composite Stock Price Index (IHSG) is one of the key indicators for gauging the condition of the capital market as well as the Indonesian economy in general. Movements in the IHSG are influenced by macroeconomic factors, including interest rates and exchange rates. Changes in interest rates can affect investors’ investment decisions, while fluctuations in exchange rates have the potential to impact corporate performance and foreign capital flows, which ultimately affect the movement of the IHSG. This study aims to analyze the impact of interest rates and exchange rates on the IHSG in Indonesia, using a descriptive literature review method based on 20 relevant scientific articles from 2024 to 2026. The results of the study found that interest rates have a negative and significant impact on the IHSG. This indicates that interest rate hikes tend to dampen stock market performance, as investors prefer investment instruments that offer more certain rates of return. Meanwhile, the exchange rate has no significant impact on the IHSG, suggesting that exchange rate fluctuations during the study period have not had a meaningful effect on the IHSG. These findings underscore that maintaining interest rate stability must be a top priority and aligned with exchange rate conditions, as this is crucial for sustaining the performance of the Indonesian stock market. Additionally, investors can use information regarding interest rate changes as one factor in their investment decision-making.